Towards Imaging Remission: Determining an MRI Inflammatory Activity-Acceptable State in RA - Rizzo, Toni (MD Conference Express, 2012)
This article discusses results from a series of studies that assessed the use of magnetic resonance imaging (MRI) to identify subclinical inflammation. The objectives of the study were to define the MRI characteristics of clinical remission and low disease activity (Outcome Measures in Rheumatoid Arthritis Clinical Trials [OMERACT] 10 criteria), to determine the predictive factors for structural progression in these patients, and to identify an MRI cutoff for nonprogression.